ATM c.7570G>C is a high-risk allele for breast cancer - Kankuri-Tammilehto Minna; Terväsmäki Anna; Kraatari-Tiri Minna; Rahikkala Elisa; Pylkäs Katri; Kuismin Outi (WILEY, 2022)
ATM is generally described as a moderate-risk breast cancer susceptibility gene. However, some of ATM variants might encounter higher risk. ATM c.7570G>C, p.Ala2524Pro, (rs769142993) is a pathogenic Finnish founder variant causative for recessively inherited ataxia-telangiectasia. At cellular level, it has been reported to have a dominant-negative effect. ATM c.7570G>C has recurrently been described in Finnish breast cancer families and unselected case cohorts collected from different parts of the country, but the rarity of the allele (MAF 0.0002772 in Finns) and lack of confirming segregation analyses have prevented any conclusive risk estimates. Here, we describe seven families from genetic counseling units with ATM c.7570G>C variant showing co-segregation with breast cancer. Further analysis of the unselected breast cancer cohort from Northern Finland (n = 1822), a geographical region previously indicated to have enrichment of the variant, demonstrated that c.7570G>C significantly associates with breast cancer, and the risk is estimated as high (odds ratio [OR] = 8.5, 95% confidence interval [CI] = 1.04-62.46, P = .018). Altogether, these results place ATM c.7570G>C variant among the high-risk alleles for breast cancer, which should be taken into consideration in genetic counseling.